Isotopic analysis method (δ13C) in apple-flavoured soft drinks - Figueira, Ricardo [UNESP]; Ducatti, Carlos [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (Institute of Food Technology, 2010)
The objective was to develop an isotopic analysis method to quantify carbon from the C3 photosynthesis cycle in apple-flavoured soft drinks. The beverage was produced in the laboratory according to Brazilian law. Adulterated soft drinks were also produced containing quantities of clarified juice below the legal limit. The isotopic analyses measured the relative isotopic enrichment of the apple soft drinks and their purified sugar fractions. From these results the quantity of source C3 was estimated by means of the isotopic dilution equation. To determine the existence of adulteration in commercial soft drinks, it was necessary to create a legal limit according to Brazilian law. Three commercial brands of soft drinks were analyzed and one was classified as adulterated. The method developed was proved to be efficient to measure the quantity of carbon from a C3 source in commercial appleflavoured soft drink. The legal limit was an important methodological innovation which enabled the identification of beverages in conformity with Brazilian law. By following the steps of the present work, this methodology can be applied to other clarified fruit beverages as a means to verify their legality.
Método de análise isotópica (δ13C) em refrigerante de maçã
Keywords: Legislation; Adulteration; Fruit; Quality; Carbon-13; IRMS; Legislação; Adulteração; Fruta; Qualidade; Carbono-13; IRMS